2004
DOI: 10.1590/s0104-66322004000100010
|View full text |Cite
|
Sign up to set email alerts
|

A new role for reduction in pressure drop in cyclones using computational fluid dynamics techniques

Abstract: -In this work a new mechanical device to improve the gas flow in cyclones by pressure drop reduction is presented and discussed. This behavior occurs due to the effects of introducing swirling breakdown phenomenon at the inlet of the vortex finder tube. The device consists of a tube with two gas inlets in an appositive spiral flux that produces a sudden reduction in the tangential velocity peak responsible for practically 80 % of the pressure drop in cyclones. In turn, peak reduction causes a decrease in press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 3 publications
0
7
0
4
Order By: Relevance
“…Ficici et al (2010) found the effect of vortex finder on pressure drop. Several works are carried out to minimize pressure drop (Noriler et al 2004;Fassani and Goldstein 2000;Kharoua et al 2011;Elsayed and Lacor 2010;Derksen and Van den Akker 2008). Avci and Karagoz (2001) theoretical analyze the pressure losses under the consideration of geometrical and flow parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Ficici et al (2010) found the effect of vortex finder on pressure drop. Several works are carried out to minimize pressure drop (Noriler et al 2004;Fassani and Goldstein 2000;Kharoua et al 2011;Elsayed and Lacor 2010;Derksen and Van den Akker 2008). Avci and Karagoz (2001) theoretical analyze the pressure losses under the consideration of geometrical and flow parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A number of deswirlers have been investigated experimentally and only one numerically , but their effects on cyclone performance are somewhat contradictory and further investigations are needed. For example, Shepherd and Lapple experimentally analyzed a cyclone fitted with straightening vanes with curved blades as well as vanes with straight vertical blades.…”
Section: Introductionmentioning
confidence: 99%
“…Untwisting devices placed at the gas outlet, such as evasés and others, are assumed to not affect the cyclone separation efficiency . Noriler et al numerically investigated the fluid flow in two types of cyclones fitted with a mechanical device for reducing pressure drop. They found that the device decreased the cyclone pressure drop by more than 20 %.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, métodos de avaliações experimentais requerem um alto investimento, sendo assim, os códigos de CFD têm sido uma alternativa para tais avaliações, tendo em vista o grande potencial em predizer o escoamento característico dos ciclones. Potencial esse, apresentados em trabalhos como Noriler et al (2004), Gimbun et al (2005) e Chu et al (2011).…”
Section: Introductionunclassified